Izzivi visokošolskih učiteljev pri spodbujanju kritičnega mišljenja – sistematični pregled literature - Makovec, Nataša (Sodobna pedagogika, 2025)
The development of critical thinking is a fundamental objective of higher education; however, this concept remains underexplored and inadequately defined, particularly regarding teaching methods and the measurement of outcomes. A review and analysis of 18 scientific articles published within the last five years revealed that the challenges faced by higher education teachers can be broadly categorized into issues related to teacher preparedness for fostering critical thinking, the influence of political and social contexts, student-related factors and the lack of a clear definition and methodological framework for critical thinking. Active work methods, such as collaborative, action-based, problem-based, and dialogical learning, as well as other student activities, have been proven to enhance the development of critical thinking. Digitalization presents both a challenge and an opportunity for teachers in implementing various activities and work methods with students, through which critical thinking can be encouraged. Future research opportunities lie in examining strategies to encourage critical thinking in students and teachers, as well as in defining a methodology that would establish standards and criteria for assessing its effectiveness.
Keywords: critical tkinking; higher education teachers; izzivi pri poučevanju; kritično mišljenje; metode dela; teaching challenges; teaching methods; visokošolski učitelji